2000
DOI: 10.1016/s0925-4773(00)00240-9
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus frizzled 7 can act in canonical and non-canonical Wnt signaling pathways: implications on early patterning and morphogenesis

Abstract: Here we report the cloning of a Xenopus frizzled transmembrane receptor, Xfz7, and describe its expression pattern during early embryogenesis. Xfz7 mRNA is provided maternally and zygotic transcription peaks in gastrula stages. At that time, transcripts are preferentially localized to the marginal zone and become restricted to distinct regions of the tadpoles in tailbud stages. Overexpression of Xfz7 in embryos perturbs the morphogenesis of trunk and tail, blocks convergence-extension movements in animal caps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(129 citation statements)
references
References 46 publications
5
124
0
Order By: Relevance
“…Inhibition of canonical Wnt signalling by a dominant-negative form of Tcf3 does not inhibit neural crest migration (F. Romero and R.M., unpublished). There is convincing experimental evidence that shows that canonical Wnt signalling is involved in neural crest induction and cell differentiation (Dorsky et al, 1998;Garcia-Castro et al, 2002;LaBonne and Bronner-Fraser, 1998;Lee et al, 2004 (CarreiraBarbosa et al, 2003;Djiane et al, 2000;Kuhl et al, 2000;Medina et al, 2000;Sumanas and Ekker, 2001;Wang and Malbon, 2004;Winklbauer et al, 2001). We have shown that Fz7 is expressed in the premigratory neural crest just before migration, as well as in the migrating neural crest.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Inhibition of canonical Wnt signalling by a dominant-negative form of Tcf3 does not inhibit neural crest migration (F. Romero and R.M., unpublished). There is convincing experimental evidence that shows that canonical Wnt signalling is involved in neural crest induction and cell differentiation (Dorsky et al, 1998;Garcia-Castro et al, 2002;LaBonne and Bronner-Fraser, 1998;Lee et al, 2004 (CarreiraBarbosa et al, 2003;Djiane et al, 2000;Kuhl et al, 2000;Medina et al, 2000;Sumanas and Ekker, 2001;Wang and Malbon, 2004;Winklbauer et al, 2001). We have shown that Fz7 is expressed in the premigratory neural crest just before migration, as well as in the migrating neural crest.…”
Section: Discussionmentioning
confidence: 49%
“…Although no specific Wnt11 receptor has been identified, there is some evidence that suggests that PCP Wnt signalling involves Fz7 (Carreira-Barbosa et al, 2003;Djiane et al, 2000;Medina et al, 2000;Sumanas and Ekker, 2001;Winklbauer et al, 2001). We examined the distribution of the Fz7 receptor in neural crest cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific domains of Dsh, PDZ, and DEP, are required for the Wnt/ PCP pathway in CE movements during vertebrate gastrulation (Djiane et al, 2000;Heisenberg et al, 2000;Medina et al, 2000;Tada and Smith, 2000;Wallingford et al, 2000). The DEP domain deletion mutant of Dsh (Dsh-⌬DEP) has DN effects on JNK activation (Boutros et al, 1998;Li et al, 1999;Moriguchi et al, 1999) and regulation of CE movements in the Wnt/PCP pathway Wallingford et al, 2000).…”
Section: Rhoa Is Essential For the Control Of Ce Movements Mediated Bmentioning
confidence: 99%
“…For example, Wnt-11 regulates CE movements by means of Frizzled (Fz) and Dishevelled (Dsh; Heisenberg et al, 2000;Tada and Smith, 2000), which resembles PCP signaling pathway in flies. Furthermore, the specific domains of Dsh (Wharton, 2003) required for PCP signaling in CE movements during vertebrate gastrulation (Djiane et al, 2000;Heisenberg et al, 2000;Medina et al, 2000;Tada and Smith, 2000;Wallingford et al, 2000) are identical to those required in Drosophila (Axelrod et al, 1998;Boutros et al, 1998;Boutros and Mlodzik, 1999). In addition, CE movements in both Xenopus and zebrafish are controlled by the core PCP genes, including RhoA/Rac1 (Habas et al, 2001(Habas et al, , 2003Tahinci and Symes, 2003), JNK (Yamanaka et al, 2002), Rho-associated kinase-2 (ROK2, Marlow et al, 2002), Strabismus (Stbm, Darken et al, 2002;Goto and Keller, 2002;Jessen et al, 2002;Park and Moon, 2002), and Prickle (Takeuchi et al, 2003;Veeman et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%